Flexural capacity calculation of RC beams strengthened with prestressed CFRP sheets - Nguyen Dang Dai Nam; Ho Manh Hung; Doan Cong Chanh; Phan Hoang Nam; Nguyen Minh Hai; Gianluca Quinci (Tạp chí Khoa học và Công nghệ)
This paper investigates flexural behavior and analytical approach for predicting the load and deflection at critical performance points of reinforced concrete (RC) beams strengthened with prestressed carbon fiber-reinforced polymer (CFRP) sheets. A finite element model is developed to simulate the interaction between the RC beam and the CFRP sheets, capturing key aspects such as failure modes, ultimate load, and mechanical behavior across the three phases of failure. The analysis reveals that increasing the prestress level significantly enhances the performance, delaying the initiation of cracking, steel yielding, and increasing the ultimate load capacity. Two distinct failure modes are identified, i.e., concrete crushing in the compressive zone and composite plate peeling. An analytical approach is then proposed to estimate the load corresponding to initial cracking, steel yielding, and ultimate failure. Comparison between the experimental, numerical and analytical results shows that the proposed method accurately predicts the flexural capacity of RC beams strengthened with prestressed CFRP sheets.